Bonus oder Bias? Mechanismen geschlechtsspezifischer Entlohnung - Juliane Achatz; Hermann Gartner; Timea Glück (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2004)
To what extent is the gender wage gap of fulltime employees due to differences in productiv-ity- related characteristics, to discrimination of female employees, and how is the wage gap affected by firm specific features? To analyze these problems we use a linked employer-employee database for East and West Germany in 2000, made available by the Institute for Labour Market Research. In particular, we address the effect on wage levels of the sex com-position of occupations within firms (job cells). Our estimations rely on the decomposition of the wage differential proposed by Oaxaca and Blinder. We find that only one tenth of the gender gap in wages is explained by human capital differences between men and women. Re-garding the gender wage gap in Germany we conclude that discrimination in the allocation of men and women to different jobs is an important mechanism: With increasing proportions of women within job cells we observe decreasing wage levels for men and women but with higher rates of decline for women than for men. While the presence of worker's councils are shown to have a positive impact on wage levels, women are found to profit most from their presence within firms.
Keywords: J16; J31; J71; 330; Lohnunterschied - Determinanten; erwerbstätige Frauen; erwerbstätige Männer; Arbeitsproduktivität; Qualifikationsniveau; Betriebsrat; regionaler Vergleich; IAB-Linked-Employer-Employee-Datensatz; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland; Lohndifferenzierung; Geschlecht; Humankapital; Arbeitsproduktivität; Deutschland; Geschlechterdiskriminierung